2022-RA-779-ESGO How frequently benign uterine myomas appear as suspicious sarcomas on ultrasound examination. (20th October 2022) - Manzour, Nabil; Guerriero, Stefano; Cabezas, Nieves; Diaz, Patricia; Lopez-Pincazo, Ana; Redondo, Ana; Springer, Serena; Pagliuca, Mariachiara; Pazcual, Maria Angela; Chacon, Enrique; Boria, Felix; Minguez, Jose Angel; et al.
Abstract : Introduction/Background: To determine the percentage of benign myomas that appear as suspicious for uterine sarcoma on ultrasound examination Methodology: Prospective observational multicenter study (June 2019-December 2021) comprising a consecutive series of patients with histologically proven uterine myoma after hysterectomy or myomectomy who underwent transvaginal and/or transabdominal ultrasound prior to surgery. All ultrasound examinations were performed by expert examiners. MUSA criteria were used to describe the lesions. Suspicion of sarcoma was established when three or more sonographic features described by Ludovisi et al as frequently present in uterine sarcoma were present. These features were no myometrium visible, irregular cystic areas, non-uniform echogenicity, irregular contour, cooked appearance and color score 3–4. In addition, the examiners had to classify the lesion as suspicious by her/his impression, independently of the number of features present. Results: 651 women were included. Median maximum diameter of the myomas was 48 mm (range: 10- 263 mm). 266 (41%) of the patients had more than one myoma. Using the criterion of > 3 suspicious features, 24 (3.7%) of the myomas had suspicious appearance. If we had used a criterion of > 2 features, this figure increased to 62 (9.5%) cases. By subjective impression, the examiners considered as suspicious 35 (5.4%) cases (18 cases had > 3 suspicious features and 29 cases had > 2 suspicious features) Conclusion: About 4–10% of benign uterine myomas may exhibit sonographic suspicion of sarcoma. This figure is not negligible.